Kejadian Penyakit Jantung Koroner pada Penderita Diabetes Mellitus - Utami, Nur Lissa; Azam, Mahalul (HIGEIA (Journal of Public Health Research and Development), 2019)
Coronary heart disease was ranked as the second cause of death in Indonesia in 2014. The purpose of this study was to determine the factors associated with the incidence of CHD in patients with DM in Kardinah Hospital Tegal. This type of research is analytic observational with case control design. Samples were taken as many as 55 cases and 58 controls by purposive sampling technique. Data were analyzed by chi square test for bivariate test and logistic regression for multivariate test. The results of the study were the relationship between age (p value=0.034,OR=2,873), family history of CHD (p value = 0.032, OR = 2.463), duration of DM (p value=0.046,OR=2.31), history of phisically activity (p value=0.043,OR=3,077), consumption of fruits and vegetables (p value=0.047,OR=2,448), consumption of fatty (p value=0,049,OR=2,277), history of obesity (p value=0,000,OR=5,391), history of dyslipidemia(p value=0.004,OR=3,338), history of hypertension(p value=0.026,OR=2,566) DM diet (p value=0.021,OR=2,531). While there is no relationship between sex, education, occupation, smoking history, duration of smoking, consumption of salty foods, coffee consumption, history of stress, and health insurance.